Determinants of prehospital coronary heart disease death - Amann, Ute; Heier, Margit; Thilo, Christian; Linseisen, Jakob; Meisinger, Christa (Scientific reports, 2021)
Limited data on prehospital and early in-hospital coronary heart disease (CHD) deaths is available. Aims of this study were to provide a comprehensive description on CHD cases and to analyse determinants of prehospital death. From a population-based myocardial infarction (MI) registry in Augsburg, Germany we included 12,572 CHD cases aged 25–74 years between 2003–2017 and 4754 CHD cases aged 75–84 years between 2009–2017. Multivariable logistic regression models were conducted to identify patient characteristics associated with prehospital death compared to 28-day survival. In patients aged 25–74 years, 1713 (13.6%) died prehospital, 941 (7.5%) died within the first 24 h in-hospital and 560 (4.5%) died within the 2nd and 28th day after the acute event; in patients aged 75–84 years the numbers were 1263 (26.6%), 749 (15.8%) and 329 (6.9%), respectively. In both age groups increasing age, actual smoking or nicotine abuse, previous MI, angina pectoris and previous stroke were more likely and hypertension was less likely in cases, who died prehospital compared to 28-day survivors. For example, in the 25–74 years old we revealed an adjusted odds ratio (OR) of 4.53 (95% CI 3.84–5.34) for angina pectoris and an OR of 0.69 (95% CI 0.57–0.85) for hypertension. In cases aged 25–74 years, an association of living alone (OR 1.26, 95% CI 1.06–1.49) and diabetes (OR 1.20, 95% CI 1.03–1.41) with prehospital death was found. Whereas in cases aged 75–84 years, chronic obstructive pulmonary disease (OR 2.20, 95%CI 1.69–0.2.85) was associated with prehospital death. In summary, we observed high prehospital and early in-hospital case fatality. Besides classical cardiac risk factors, the impact of living alone on prehospital death was more important in patients aged 25–74 years than in older patients.